2017
DOI: 10.1534/genetics.117.201939
|View full text |Cite
|
Sign up to set email alerts
|

Residues in the Nucleosome Acidic Patch Regulate Histone Occupancy and Are Important for FACT Binding in Saccharomyces cerevisiae

Abstract: The essential histone chaperone FACT plays a critical role in DNA replication, repair, and transcription, primarily by binding to histone H2A-H2B dimers and regulating their assembly into nucleosomes. While FACT histone chaperone activity has been extensively studied, the exact nature of the H2A and H2B residues important for FACT binding remains controversial. In this study, we characterized the functions of residues in the histone H2A and H2B acidic patch, which is important for binding many chromatin-associ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 39 publications
2
11
0
Order By: Relevance
“…The detection of peptides for Spt16 was intriguing to us because we previously reported that the acidic patch is required for proper histone occupancy as well as Spt16 occupancy on genes in vivo (9). A recent study also showed a reduction in co-immunoprecipitation between Spt16 and H2A from yeast cell extracts when certain acidic patch residues were substituted with alanine (83). We confirmed our mass spectrometry results by western blot analysis, which demonstrated UV- and BPA-specific crosslinking between Spt16-3XMyc and H2A-A61 BPA (Figure 4).…”
Section: Resultsmentioning
confidence: 99%
“…The detection of peptides for Spt16 was intriguing to us because we previously reported that the acidic patch is required for proper histone occupancy as well as Spt16 occupancy on genes in vivo (9). A recent study also showed a reduction in co-immunoprecipitation between Spt16 and H2A from yeast cell extracts when certain acidic patch residues were substituted with alanine (83). We confirmed our mass spectrometry results by western blot analysis, which demonstrated UV- and BPA-specific crosslinking between Spt16-3XMyc and H2A-A61 BPA (Figure 4).…”
Section: Resultsmentioning
confidence: 99%
“…FACT was observed to promote transitions from tetranucleosomes to linear strings of nucleosomes, which should significantly facilitate transcription [93]. Another study showed that FACT could bind the acidic histone patch on the nucleosome, which is the surface on the planar side of the nucleosome "disk" that faces the neighboring nucleosome, and also proposed a mechanism of FACT-mediated tetranucleosome unfolding [94]. These models for decondensation of higher order structures do not exclude the activities described above, rather they could work together in a cooperative manner.…”
Section: Fact In Transcriptionmentioning
confidence: 99%
“…The histone acidic patch is a region of the nucleosome composed of eight H2A amino acid residues and two H2B residues which together create a highly negatively charged surface on the nucleosome, in contrast to the rest of the nucleosome surface, which is positively charged to promote interaction with DNA (Luger et al, 1997). The acidic patch is a hotspot for interacting factors, including the SAGA coactivator (Morgan et al, 2016), the DOT1L H3K79 histone methyltransferase (Anderson et al, 2019), the Kaposi's sarcoma herpesvirus LANA (Barbera et al, 2006), the PAF1 complex member RTF1 (Cucinotta, Hildreth, McShane, Shirra, & Arndt, 2019), the E3 ubiquitin ligase RNF168 (Mattiroli, Uckelmann, Sahtoe, van Dijk, & Sixma, 2014), the Polycomb complex PRC1 (McGinty, Henrici, & Tan, 2014), the FACT histone chaperone (Hodges, Gloss, & Wyrick, 2017), and the histone H4 tail (Fan, Rangasamy, Luger, & Tremethick, 2004;Kalashnikova, Porter-Goff, Muthurajan, Luger, & Hansen, 2013). Many factors bind the acidic patch by an "arginine anchor" motif (McGinty et al, 2014).…”
Section: Nucleosomes Are Formed From Dna Interacting With An Octamer mentioning
confidence: 99%